2021
DOI: 10.1097/acm.0000000000004243
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Health Care Access and Satisfaction Across Intersections of Race/Ethnicity and Sexual Identity

Abstract: PurposeRacial/ethnic and sexual minorities experience numerous health disparities compared with their White and heterosexual counterparts, which may be exacerbated when these social identities intersect. The authors tested for differences in health care access and satisfaction across intersections of sexual identity and race/ethnicity. MethodA cross-sectional secondary data analysis of the 2012-2018 waves of the Association of American Medical Colleges biannual online Consumer Survey of Health Care Access was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…4 Decreased access to STI testing and sexual health services among Hispanic MSM due to the pandemic may exacerbate existent health care access disparities. 30 The pandemic experience of these self-selected persons in these 5 cities may be different than a population-based sample and may be different in other regions of the country. It is a strength that these data come from both mid-sized and large metro areas in noncoastal cities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…4 Decreased access to STI testing and sexual health services among Hispanic MSM due to the pandemic may exacerbate existent health care access disparities. 30 The pandemic experience of these self-selected persons in these 5 cities may be different than a population-based sample and may be different in other regions of the country. It is a strength that these data come from both mid-sized and large metro areas in noncoastal cities.…”
Section: Discussionmentioning
confidence: 94%
“…During the pandemic, California surveillance data indicated that one of the largest declines in STI case reporting occurred in Hispanic persons with fewer cases of chlamydia, gonorrhea, nonprimary/nonsecondary syphilis, and unknown/late syphilis cases reported in the first half of 2020 compared with the same time period in 2019 4 . Decreased access to STI testing and sexual health services among Hispanic MSM due to the pandemic may exacerbate existent health care access disparities 30 …”
Section: Discussionmentioning
confidence: 99%
“…Intersectionality, increasingly recognized as an important tool for health equity research, considers individuals with multiple marginalized identities who are subject to interactive mechanisms of oppression. 3,4,58,[62][63][64][65] There is limited consensus on best practices in education and training for providers to gain competency in structural racism, racial biases, intersectionality, and how these biases contribute to downstream health inequities. Research demonstrates that health systems and the providers within the systems espouse egalitarian views but concurrently manifest racial biases, which are associated with differential treatment, lower patient satisfaction, and ultimately delays in seeking care.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Currently, disparities in health care for gender and sexual minorities remains a pressing topic. 3 However, most application services and diversity reports fail to recognize these variables as elements of diversity. The importance of physicians being representative of the population remains true for gender and sexual minorities.…”
Section: To the Editormentioning
confidence: 99%